Analisis Dampak Pertumbuhan Penduduk, Tingkat Pendidikan, Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Kota Langsa - Anggi Pratiwi; Ika Mulyani; Safuridar Safuridar; Puti Andiny (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Development can be driven by the population as the subject of development itself, and economic growth will increase if the population has high quality productivity. This research aims to analyze the impact of population growth, occupational education levels and also the workforce in Langsa City. . In this research, the data used is panel time series data.. This research uses the Pearson correlation approach method using the SPSS version 23 application. The results of the research show that the Population Growth variable (X1) is negatively related to economic growth with a strong correlation level in Langsa City; the Education Level variable (X2) is negatively related to economic growth with a moderate level of correlation; and the labor variable (X3) is negatively related to economic growth with a weak correlation in Langsa City. However, it should be remembered that the influence of labor on economic growth can vary depending on the conditions and other factors that exist in an area.